Communication and Peace - Hamelink, Cees J. author. aut Link
XVII, 161 p. 1 illus.
Keywords: This book provides a robust conceptualization of peace. Hamelink defines peace as conceived of moments of celebrating human togetherness, with deep fractures that polarize society standing in the way of collectively celebrating togetherness and posing a serious existential risk to humanity. ‘Deep dialogue’ is the form of human cooperative communication that is needed to build communities that can overcome polarization. This is the most difficult form of human conversation as it is based upon trust, mutuality, patience and freedom, and requires safe, non-threatening spaces, but this book explains how to overcome the essential obstacles that prevent this dialogue. To curate a ‘deep dialogue’ we must turn to humanity’s unique resource: our ability to communicate pro-socially and cooperatively.